A multicenter phase II randomized study of Cremophor‐free polymeric nanoparticle formulation of paclitaxel in women with locally advanced and/or metastatic breast cancer after failure of anthracycline. Issue 2 (26th November 2012) - Ranade, Anantbhushan A; Bapsy, Poonamalle P; Nag, Shona; Raghunadharao, Digumarti; Raina, Vinod; Advani, Suresh H; Patil, Shekhar; Maru, Anish; Gangadharan, Vadavattath Padmanabhan; Goswami, Chanchal; Sekhon, Jagdev Singh; Sambasivaiah, Kuraparthy; et al.
Abstract Aims Paclitaxel is extensively used in the treatment of advanced carcinomas of the breast, ovary and non‐small cell lung cancer. In clinical use it is formulated in the non‐ionic surfactant polyethoxylated castor oil (Cremophor) and dehydrated alcohol to enhance drug solubility. Cremophor adds to toxic effects of paclitaxel by producing or contributing to the well‐described hypersensitivity reactions that commonly occur during its infusion, affecting a large number of patients. This randomized trial was conducted to evaluate efficacy and safety of novel nanoparticle‐based paclitaxel in the treatment of patients with advanced breast cancer. Method Patients were randomized to receive either nanoparticle paclitaxel (NP) 300 mg/m2, (NP300) or NP220 mg/m2 or Cremophor paclitaxel 175 mg/m2 (CP 175). NP was administered as a 1‐h infusion without premedication and CP as a 3‐h infusion with premedication every 3 weeks. Results In total, 194 patients who had been administered at least one dose were included for safety analysis and 170 patients who completed at least two cycles of therapy were analyzed for efficacy. NP showed an overall response rate (complete response + partial response) of 40% in the NP220 and NP300 arms as compared to 31% in the CP arm. The incidence of neutropenia (all grades) was lowest in the NP220 arm (39.4%) compared to the NP300 (55%) and CP arm (50%). Conclusion NP is well tolerated and can be safely administered without any premedication in comparison to conventional paclitaxel, which requires the use of premedication before administration. NP demonstrates promising efficacy with a favorable safety profile.